Atypical leukoencephalopathy due to a snake bite in a pregnant patient: MRI findings - Ayla Ozaydogdu Cimen (Medicine Science)
Snake envenomation significantly contributes to morbidity and mortality. Although various clinical presentations and complications are observed with different snake bites, the incidence of leukoencephalopathy is rare. Most cases of leukoencephalopathy occur following viper bites. In this article, we present a rare case of multiple infarctions and leukoencephalopathy involving the corona radiata and centrum semiovale following a neurotoxic snake bite. We emphasize the importance of considering this complication, albeit rare, in cases of snake envenomation. [Med-Science 2025; 14(1.000): 294-6]